Changes in LEND trainees’ understanding and application of diversity, equity, inclusion, and justice principles - Fisher, Allison P.; Gies, Lisa M.; Weber, Stephanie; Froehlich, Tanya; Abimosleh, Simon; Ravindran, Neeraja; Smith, Jennifer (Frontiers in Pediatrics, 2024)
Objectives: To assess changes in trainees' knowledge and application of Diversity, Equity, Inclusion, and Justice (DEIJ) concepts after participating in a midwestern academic medical center Leadership Education in Neurodevelopmental and Related Disabilities (LEND) program. LEND is a federally funded year-long program training individuals of various disciplines (e.g., speech pathology, family advocacy, psychology) to better support the health of individuals with disabilities.Methods: Trainees (n=46) answered questions about their knowledge and application of DEIJ topics before and after program participation in 2021-2022 and 2022-2023. Changes in trainees' responses were examined using paired-samples t-tests.Results: Thirty-six (78%) participants identified as White, 7 (15%) as Black, 2 (4%) as Asian, and 2 (4%) as more than one race. Three (7%) participants identified as Hispanic/Latino. Over the one-year program, trainees' perceived knowledge increased (t(45)=5.84, p < .001, Mdiff = .59, Cohen's D = 0.86). Regarding articulating definitions of DEIJ terms, trainees' summed scores following program participation also improved (t(45)=4.71, p < .001, Mdiff = 2.37, Cohen's D = 0.70). However, their comfort with addressing prejudicial statements and discussing and combating "-isms" (application of DEIJ skills) did not increase (t(45) = 1.74, p = .09, Mdiff = 0.17, Cohen's D = 0.26).Conclusions for Practice: LEND program participation positively impacted trainees' perceived DEIJ knowledge and ability to define DEIJ terms. However, future refinements to the curriculum will be needed to improve trainees' application of skills and to develop a more nuanced understanding of equity, intersectionality, inclusion, and belonging.